Analisis fungsi dan isi pantun masyarakat Desa Kopong dan relevansinya terhadap pembelajaran Bahasa Indonesia di SMP - Robertus Adi Sarjono Owon; Maria Ermelinda Dua Lering (University of Muhammadiyah Malang, 2021)
This research aimed to analyze the function and content of community limerick in Desa Kopong, Kecamatan Kewapante, Kabupaten Sikka. Spoken literature works are largely practiced in this community to transfer messages among people. This research employed a qualitative approach with a descriptive method. The obtained data were in the form of rhymes and verses obtained from engagement techniques and participant observation. The obtained data were analyzed through content analysis techniques and data validation with triangulation methods. Results showed that the community limerick in Desa Kopong functions as a means of recreation, aesthetics, didactic, morality, and religion. The content of the limericks includes reinforcement of the values ​​of grit, resilience, politeness, volunteerism, and religion. Finding from this research is significant for Bahasa Indonesia (BI) lesson in junior high schools (SMP), especially related to students’ competency in analyzing the forms and contents of community limerick.